DISTRIBUSI DAN INVENTARISASI KEANEKARAGAMAN JENIS BURUNG DI KAWASAN KAMPUS UNIVERSITAS SULAWESI BARAT DAN SEKITARNYA - Alexander Kurniawan Sariyanto Putera; Isdaryanti Isdaryanti (Universitas Patompo, 2022)
This study elucidates the diversity of birds at the University of West Sulawesi, a region that is part of the Wallacea ecosystem, renowned for its biodiversity. The research involved an inventory of 22 bird species belonging to 17 families, with a total of 180 individuals. Among the observed species, 7 were found distributed across various habitat types, while 13 others were located in habitats less influenced by human activities, such as grasslands, shrubs, and trees. Interestingly, 2 species, Perkutut Jawa and Kacamata Sulawesi, were exclusively found in habitats frequently affected by human activities, like settlements and plantations. The study also reveals that approximately 27.27% of the 22 observed bird species are Sulawesi endemics, while 72.73% are non-Sulawesi endemics. These findings offer crucial insights into the composition and distribution of birds in the research area and have significant implications for conservation efforts. Protecting natural habitats, especially for endemic species, should be a priority. Additionally, a better understanding of how birds interact with human-affected habitats is necessary to develop effective conservation strategies. Further studies on specific species may be required in environments increasingly fragmented by human activities. Advancing knowledge in ornithology is the key to preserving bird diversity in Wallacea.